Motivasi Psikologi Kerelawanan Komunitas Rumah Kreatif Wadas Kelir - Imam Hidayat; Heru Kurniawan; Mukhamad Hamid Samiaji (Universitas Mathla'ul Anwar Banten, 2021)
MOTIVATIONAL PSYCHOLOGY VOLUNTEERING CREATIVE HOME COMMUNITY WADAS KELIR. The purpose of this study is to explore the phenomenon of motivational psychology of individual volunteerism in conducting educational and community literacy services in the Wadas Kelir Creative House community. Found five motivations of volunteerism that become the basis of one's willingness to do and develop various educational and literacy devotional activities in the community of Rumah Kreatif Wadas Kelir. The five motivations of volunteerism are (1) the motivation of volunteering and doing volunteering activities because of parents; (2) the motivation of volunteerism as an effort to manifest an idealistic figure for himself; (3) the motivation of the hero in the hope to gain skills to work in achieving achievements; (4) the motivation of volunteerism as an effort to realize the dream of achieving high expectations; and (5) volunteer motivation in actualizing themselves to learn direct practice in the community.